Activation of Brain Regions Associated with Working Memory and Inhibitory Control in Patients with Attention-Deficit/Hyperactivity Disorder in Functional Near-Infrared Spectroscopy: A Systematic Review - Hou, Lihao; Yang, Jiaxuan; Xu, Lin; Peng, Juanjuan; Joyce Law, Cho Y.; Chen, Tianhao (Current Medical Imaging, 2023)
Introduction: Patients with attention-deficit/hyperactivity disorder (ADHD) often show abnormalities related to cognitive activities, especially related to working memory and inhibitory control. Functional near-infrared spectroscopy (fNIRS) is a non-invasive brain imaging technique based on the changes in cerebral hemodynamics to measure the response of brain activities to cognitive tasks. Methods: In this review, we collected all clinical experiments that evaluated the changes of oxyhemoglobin levels in relevant brain regions of patients with ADHD through cognitive tasks by fNIRS to determine the abnormalities of brain regions related to working memory and inhibitory control activities in patients with ADHD. Results: From the beginning of November 2021, PubMed, PsycINFO, Scopus, EMBASE, CINAHL, web of science and Cochrane library were searched, and ROBINS-I was a tool to evaluate the quality and risk bias of the articles included. Sixteen eligible clinical trials or randomized controlled trials were included, of which six measured working memory and eleven measured inhibitory control. Conclusion: We found that compared with healthy people, the activation scope of working memory and inhibition control in the frontal cortex in ADHD patients was smaller than that in healthy people, and the activation degree was weak or even inactive, which can provide new ideas for the direction of research on ADHD.
Keywords: working memory